2014
DOI: 10.4028/www.scientific.net/kem.611-612.1079
|View full text |Cite
|
Sign up to set email alerts
|

Hot Single Point Incremental Forming of Ti-6Al-4V Alloy

Abstract: The lightweight metal alloy Ti-6Al-4V is widely used in the aeronautical industry due to its excellent mechanical properties. However, it is known the difficulty to deform Ti-6Al-4V sheets at room temperature because of its microstructure conditions. The present work focuses on the evaluation of formability of Ti-6Al-4V sheets using hot single point incremental forming (SPIF) process which it seems appropriate to produce small batches of parts due to its flexibility as it allows a significant reduction of cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
2
13
0
1
Order By: Relevance
“…Furthermore, the titanium surface is embrittled by oxygen above 540 ºC as a function of time and temperature. 4 These temperature results match well with the material behaviour observed by Ortiz et al 27 where it was concluded that the formability of Ti-6Al-4V starts enhancing drastically from 500 ºC approximately. In spite of having the more homogenous temperature distribution, T1 trial finished before obtaining the final part since the sheet broke during the forming at the final stage.…”
Section: Influence Of the Working Temperature On The Geometric Accuracysupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the titanium surface is embrittled by oxygen above 540 ºC as a function of time and temperature. 4 These temperature results match well with the material behaviour observed by Ortiz et al 27 where it was concluded that the formability of Ti-6Al-4V starts enhancing drastically from 500 ºC approximately. In spite of having the more homogenous temperature distribution, T1 trial finished before obtaining the final part since the sheet broke during the forming at the final stage.…”
Section: Influence Of the Working Temperature On The Geometric Accuracysupporting
confidence: 87%
“…In spite of having the more homogenous temperature distribution, T1 trial finished before obtaining the final part since the sheet broke during the forming at the final stage. As we observe above, the temperatures reached on the sheet in this case are not high enough to enhance the material formability as the study of Ortiz et al 27 points out. In fact, in T1 temperature is around 400 ºC so the formability is similar to that obtained at room temperature.…”
Section: Influence Of the Working Temperature On The Geometric Accuracymentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, the parts were produced at a 1000 mm/min feed rate and a 0.29 mm tool step down except at the bottom area where a 0.5 mm tool step over the part surface was used following a raster strategy. These process parameters were defined taking into account both the Ti-6Al-4V formability evaluation that previously had been carried out [14] and the part geometry. For all the trials, a ceramic wheel tool with a 11 mm forming radius and boron nitride as lubricant were chosen to provide adequate contact conditions during forming.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…Incremental forming methods, apart from shaping hollow products, are also used in forming cylindrical sheet metal products/tubes. These technologies can be also used in the production of products made of hard-deforming materials, such as titanium alloys [14,15].…”
Section: Introductionmentioning
confidence: 99%